(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The purpose of this study was to investigate the effect of a 26 week extended yoga program on the selected psychological and physiological variables of the juvenile prison inmates. Subjects aged 12-18 years old were randomly selected through simple random sampling and divided into two equal groups experimental and control (N=100). The selected criterion measured was attitude, aggression, and anxiety in psychology and blood-pressure, pulse rate, vital capacity and cardio-vascular in physiology. After the pre-data-collection experimental group underwent through 26 weeks extended yoga program and control group were left remain busy with their as usual daily casual. Pre-post data had been collected (through using standard tool and equipment using standard procedure) and analyzed the difference through independent sample ‘t’ test and ANCOVA as well, using SPSS 20.0. Finding clearly showed that, the general social attitude of the prison inmates has been improved and aggression has been moderately reduced. At the same time, inmates feel less anxious after the extended yoga program. Whereas in physiological variables blood pressure; diastolic and systolic has been reduced compare to control group but remain close to health standard value but Vital capacity and Cardio-Vascular efficiency have been significantly improved after 26 weeks of the extended yoga program. Hence it is concluded that yogic Programs can change the life of common people as well as prisoner inmates.